Numerical simulation of offshore wind power pile foundation scour with different arrangements of artificial reefs - Yang, Mingda; Tang, Yanli; Zhao, Fenfang; Xu, Shiji (Frontiers in Marine Science, 2023)
The industrial integration of offshore wind power and marine ranches has been actively explored and developed in many countries. This emerging industrial synergy model can significantly improve the ecological friendliness of offshore wind power and contribute to the high-quality development of the marine economy in the region. This industrial synergy model is an important development direction for future offshore engineering. Artificial reefs (ARs) are critical components of marine ranches and are widely placed around offshore wind foundations (OWFs). The ARs can block the water flow and form a complex wake region behind it, which changes the original turbulence structure and reduces scour around the OWF. Therefore, determining the arrangement of ARs for scour protection around an OWF is of great engineering significance. In this study, a three-dimensional numerical model is established using a prototype of the first offshore wind power-marine ranch demonstration project in China. The turbulent change and sediment movement between the OWF and ARs are solved using the Reynolds-averaged Navier-Stokes (RANS) and sediment transport equations. Moreover, the variations in the maximum scour depth and scour volume around the OWF at different arrangements of ARs are explored. The results demonstrate that the arrangement of ARs weakens the horseshoe vortices in front of the OWF and destroys the vortex shedding behind the OWF, thereby producing a beneficial scour protection effect. Various arrangements of ARs have different effects on scour results around the OWF. Increasing the height of the AR could significantly reduce the scour results around the OWF and play an effective role in scour protection, followed by the tandem arrangement of ARs, whereas the parallel arrangement of ARs will produce negative scour effects. This study will serve a vital guiding role in the arrangement of ARs and practical significance for scouring protection around the OWF.